Myter og mundtlighed - Nielsen, Vilhelm (Grundtvig-studier, 1985)
Myths and Word of Mouth Jens Peter Ægidius: Braga Talks, Norse Myths and Narrative Myths in the Danish Tradition (to 1910). Odense 1985.Reviewed by Vilhelm Nielsen. The title Braga Talks is taken from Grundtvig, who in 1843-44 gave 25 lectures under this heading; these are treated in detail by Ægidius. The phrase has since been misunderstood, however, and misused to mean words without content or basis in reality. Braga, the god of poetry, has been forgotten and the emphasis has been transferred to the word talk. The title of this book expresses a slipping from the mythology itself into its narrative reproduction. While working on the preface and the introduction to Norse Mythology (1832) Grundtvig made the discovery (as Thaning has proved) that myths are oral. This was one of the slow discoveries he made, and could have been made the main theme of this book, which says little that is new about Grundtvig’s use of his sources. It does, however, offer a great deal on the narrative tradition in use at the grundtvigian folk high schools, which has been revived in this century by Aage Møller, a clergyman and high school teacher. Unfortunately this phase has not been treated, as the book stops at 1910. Ægidius has, however, included Ludvig Christian Møller, the narrative historian, who was Grundtvig’s disciple and who even before him gave historical talks for both men and women at Borch’s hostel in the 1830s. His narration of myths and legends was only his introduction to narratives from medieval history. The other major characters in Ægidius’ book are Christian Flor and Ludvig Schrøder. Flor was originally Professor of Danish at Kiel but became principal of the first Danish folk high school at Rødding in 1844. Schr.der became principal of Askov folk high school, which from 1864 onwards carried the stamp of his personality. Ægidius claims, and the reviewer underlines this new information, that Schrøder did not give up teaching the myths, even though from 1884 onwards he went on to talk about Denmark’s natural resources. Unfortunately we have only comprehensive notes to the lectures but no myth narratives in written form from his side. His lectures on myth were apparently not the same from year to year, but they were wellprepared and reformulated every time, a necessary precondition for their being both “animated” and mythically “sound”, not in fact lectures but “proper stories”, as Grundtvig says in 1838. The reviewer looks forward to a continuation of the book to include an assessment of Aage Møller’s attempt to revive the tradition — and possibly as a guideline for the most recent trends.